Epidemiology of Infectious Diseases - Iqbal, Uqbah (Journal of Medical Health Research and Psychiatry, 2024)
Written by Dr. Irwan SKM. the author hope that this book can become one of the additional reading materials information in the field of epidemiology, especially for courses of epidemiology of infectious diseases for health faculty student’s community and other health students. Development of science and technology in the medicine field encourages experts to always carry out research against various diseases, one of which is contagious disease in order to overcome the incidence of suffering and death as a disease result. Definition of epidemiology according to the origin of the word, if reviewed the origin of the word epidemiology comes from the Greek word consisting from 3 basic words, namely Epi which means on or about, demos which means inhabitants and the last word is Logos which means Science. So epidemiology is a science that studies about residents. Meanwhile in the modern sense at the time this is a science that studies frequency and distribution (spread) and determinants of health problems in a group of people or society and their determination (factors that influence it). Infectious diseases arise as a result of the operation of various factors either from the agent, parent or the environment. This shape is depicted in terms that are widely known today. Namely multiple causes as opposed to a single cause. In the efforts of experts to collect knowledge regarding the emergence of disease, they have done controlled experiments to test the extent to which the disease can occur to prevent it so that it can improve the sufferer's standard of living.